What can a shell tell? : the story of the multiproxy bivalve Arctica islandica - G. Crippa; L. Angiolini; C. Bottini; E. Erba; F. Felletti; M.R. Petrizzo; C. Frigerio; J. A. I. Hennissen; M. J. Leng; I. Raffi; S. Raffi; G. Raineri; et al. (2015)
Fossil carbonate bivalve shells are archives which can tell us several stories. In this prospect, one of the main character of the Quaternary marine evolution is represented by the multitasking bivalve Arctica islandica; its performances range from the field of biostratigraphy, palaeoclimatology and sclerochronology, but these are only some of its numerous ‘talents’. Among bivalve molluscs, Arctica islandica is known as the Methuselah because of its remarkable lifespan of up to 500 years. It represents one of the most important boreal guests, which migrated from higher northern latitudes into the Mediterranean Sea in consequence of the climatic cooling leading to the Middle Pleistocene glaciations. For this reason, since the eighties, A. islandica was considered one of the main markers of the Pliocene-Pleistocene boundary (1.8 m.y.), remaining in office until 2010, when, the boundary was lowered at 2.6 m.y. After that it was used to mark the Gelasian-Calabrian boundary. However, A. islandica has its most significant impact in the field of palaeoclimate and palaeoenvironmental reconstructions, recording seawater changes in its shell in the form of variable growth increment widths and variable geochemical properties. It is in fact an excellent proxy for studies of ancient ocean conditions because it sensitively and faithfully records the primary seawater isotope composition with no vital effect in its shell layers. A sclerochemical study performed on A. islandica shells from the Arda River marine succession (Castell’Arquato, Northern Italy) highlights the potential of this species in recording the past seasonal variation occurred during its lifespan. This study allowed to reconstruct in details the climate evolution of the Mediterranean area prior to the Middle Pleistocene continental glaciation, showing that seasonality was the main variable involved in the climate change. The establishment of widespread populations of cold guests in the Mediterranean Sea at about 1.8 m.y. was, in fact, triggered by extreme ...